Extraction technology impacts on the structure-function relationship between sodium alginate extracts and their in vitro prebiotic activity. (October 2020) - Okolie, Chigozie Louis; Mason, Beth; Mohan, Aishwarya; Pitts, Nancy; Udenigwe, Chibuike C.
Abstract: Sodium alginate extracted from Ascophyllum nodosum using conventional chemical extraction (Alg-CCE), microwave-assisted extraction (Alg-MAE), ultrasound-assisted extraction (Alg-UAE), and a combination of both enzyme-assisted and conventional chemical extraction (Alg-EAE/CCE) methods were studied for both physicochemical properties and in vitro prebiotic activity. Alg-EAE/CCE had the highest yield, which was significantly (p < 0.05) higher than Alg-MAE and Alg-UAE. However, total uronic acids were highest in the Alg-UAE and was significantly (p < 0.05) higher than in either Alg-CCE or Alg-MAE. The average molecular weight of all extracts were within the range of 65–215 kDa and had similar dispersity index. There were no significant differences in the mannuronate to guluronate (M/G) ratio of the extracts. Higher guluronic than mannuronic acid absorbance values were observed in the extracts, thus suggesting gelling capabilities because guluronic acid preferentially binds calcium. The growth rate of Lactobacillus delbruecki ssp bulgaricus strain in supplemented growth media at 0.10, 0.30 and 0.50% (w/v), were increased in a dose-dependent manner as compared to an un-supplemented growth medium as control. Similar observations were obtained for the L. casei strain, except at the 0.50% (w/v) inclusion where the growth rate decreased. No significant impacts on short-chain fatty acids production were observed, though pH decreased further in the supplemented sodium alginate growth medium. This study indicated that alginate extracts of A. nodosum were able to show prebiotic responses in two strains of Lactobacillus although there were no significant influences of the extraction methods on the in vitro prebiotic responses.